Heavy-Metal-Free Colloidal Semiconductor Nanorods: Recent Advances and Future Perspectives - Jia, Guohua; Pang, Y.; Ning, J.; Banin, U.; Ji, B. (WILEY-V C H VERLAG GMBH, 2019)
Quasi-1D colloidal semiconductor nanorods (NRs) are at the forefront of nanoparticle (NP) research owing to their intriguing size-dependent and shape-dependent optical and electronic properties. The past decade has witnessed significant advances in both fundamental understanding of the growth mechanisms and applications of these stimulating materials. Herein, the state-of-the-art of colloidal semiconductor NRs is reviewed, with special emphasis on heavy-metal-free materials. The main growth mechanisms of heavy-metal-free colloidal semiconductor NRs are first elaborated, including anisotropic-controlled growth, oriented attachment, solution–liquid–solid method, and cation exchange. Then, structural engineering and properties of semiconductor NRs are discussed, with a comprehensive overview of core/shell structures, alloying, and doping, as well as semiconductor–metal hybrid nanostructures, followed by highlighted practical applications in terms of photocatalysis, photodetectors, solar cells, and biomedicine. Finally, challenges and future opportunities in this fascinating research area are proposed.